Application of the Workload Indicators of Staffing (WISN) Method for Optimal Staffing at Jimmy Medika Borneo Mother and Child Hospital - Rantemarampa, William Mallisa; Syaodih, Erliany; Rubini, Rizki Adriansyah (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to analyze the application of the Workload Indicators of Staffing Need (WISN) method in determining the optimal staffing requirements at Jimmy Medika Borneo Mother and Child Hospital (RSIA). In response to the significant increase in patient volume from 2021 to 2024, RSIA JMB requires an accurate human resource management strategy to avoid workload imbalances. This descriptive qualitative study involved 57 healthcare workers across 12 units, using a work sampling method involving observation and interviews with all healthcare personnel at RSIA JMB, combined with the calculation of WISN scores and ratios as recommended by the WHO. Data were collected from various service units, including emergency nurses, operating room nurses, inpatient and outpatient nurses, general practitioners, midwives in delivery and perinatal care, pharmacists, laboratory staff, and medical specialists. The results showed variations in available working time and imbalances in WISN ratios across units, with the WISN ratio varying from 0.5 to 1. Several units were overworked, including pharmacy staff, emergency nurses, operating room nurses, outpatient nurses, midwives in VK-Perina, emergency general practitioners, obstetricians and gynecologists, and surgical oncologists. In contrast, the laboratory unit was categorized as underworked, while balanced workloads were found among inpatient nurses, pediatricians, and internal medicine specialists. These findings serve as a basis for RSIA JMB management to conduct strategic evaluations and redistribute health personnel to enhance service efficiency and improve healthcare worker well-being.